Psychopathic Behavior of the Main Character in the Arabic Short Story "Camelia" by Ahmed Saber Hussein - Wulandari Wulandari; Hilman Jaelani (Indonesian Journal of Arabic Studies, 2024)
Purpose: The purpose of this study is to find out how the character who has a psychiatric disorder, and the factors causing psychopathic behavior appear in the main character in the short story "Camelia". Design/methods/ approach: This study used a literary psychology approach. This research data is in the form of quotes derived from dialogues between characters, information from other characters, and character behavior, which is a description of the author directly or indirectly. The theory used consists of Sigmund Freud's psychoanalysis, Hare's psychopathy theory, and Checkley's psychopath classification. Findings: The researcher has reached significant results, including: the main personality disorders present are (1) Anti-Social Behavior, (2) Manipulative Tendencies, (3) Aggressive Behavior, (4) Sadistic Behavior, and (5) Egocentric and a Lack of Empathy for Others. Research implication: The theory of literary psychology in this research uses the textual method, which examines the psychological aspects of personality in literary works.Â  The main character in the story of Camelia is classified as a secondary psychopath. There are two factors that influence the main character to become a psychopath, the internalÂ  and the external factor.